(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:High oxidative stress reflects the state when the production of reactive oxygen species exceeds their removal. Malondialdehyde (MDA )and Hexanoyl-Lysine Adduct (HEL) are indicators of oxidative damage of lipids caused by free radicals in blood. The high level of these biomarkers has been implicated in early pregnancy complications. Objectives:This study aimed to investigate the correlation between serum oxidative stress biomarkers in preterm and post-term deliveries. Methods:A case-control study was designed to recruit 90 pregnant women with 30 women delivering at term (control group), 30 women at preterm (first case group) and 30 women at post-term (second case group). All women underwent elective cesarean section. Blood samples were collected before admission to operation theatre. Women’s age, body mass index, lipid profile, renal function test and random glucose were measured. Serum oxidative stress biomarkers (Malondialdehyde and Hexanoyl-Lysine Adduct) were measured as indicators of lipid peroxidation. Results:The results showed that study groups were significantly different in serum MDA and HEL (P ? 0.01). Both serum MDA and HEL levels were significantly higher in preterm women group and their level steadily decreased as pregnancy progressed. Serum MDA was not significantly different between term and post-term women groups (P>0.05). Conclusions: Oxidative stress biomarkers may be important contributors of premature birth. Low level of serum HEL may play a role in delayed onset of labor. The causal relationship between oxidative stress biomarkers and pregnancy outcome may be further investigated by longitudinal studies. Key words: Oxidative Stress, Preterm women, Post-term women, Malondialdehyde, Hexanoyl-Lysine Adduct.